2007
DOI: 10.1007/s10552-007-9047-z
|View full text |Cite
|
Sign up to set email alerts
|

Diet and risk of multiple myeloma in Connecticut women

Abstract: Multiple myeloma accounts for an estimated 19,900 incident cancer cases per year in the United States. A population-based case-control study, consisting of 179 incident cases and 691 controls, was conducted to examine the impact of diet on multiple myeloma risk. Diet was assessed using a food frequency questionnaire and odds ratios, 95% confidence intervals, and P-trends were calculated across quartiles of consumption. After controlling for potential confounders, we observed inverse associations for cooked tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Our analysis included data and specimens with cases identified from the Surveillance, Epidemiology, and End Results (SEER) programs of the greater Seattle/Puget Sound and Detroit regions, as well as the Yale Comprehensive Cancer Center’s Rapid Case Ascertainment Shared Resource, a component of the Connecticut Tumor Registry [38,39]. Eligible cases were residents of the Seattle/Puget Sound region, Detroit metropolitan area, or the state of Connecticut, aged 35–74 years, with a diagnosis of MM (ICD-O-2 M9731:2) made between 2000 and 2002 in Seattle and Detroit and between 1996 and 2002 in Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis included data and specimens with cases identified from the Surveillance, Epidemiology, and End Results (SEER) programs of the greater Seattle/Puget Sound and Detroit regions, as well as the Yale Comprehensive Cancer Center’s Rapid Case Ascertainment Shared Resource, a component of the Connecticut Tumor Registry [38,39]. Eligible cases were residents of the Seattle/Puget Sound region, Detroit metropolitan area, or the state of Connecticut, aged 35–74 years, with a diagnosis of MM (ICD-O-2 M9731:2) made between 2000 and 2002 in Seattle and Detroit and between 1996 and 2002 in Connecticut.…”
Section: Methodsmentioning
confidence: 99%
“…Established risk factors include older age, male sex, African ancestry, and obesity. 2 Findings suggestive of a protective effect of alcohol consumption on MM risk are less consistent, as demonstrated in some case-control studies 3-6 and cohort investigations, 7-10 but not others. 11-14 Given the rarity of MM many of these past investigations had limited statistical power to detect an alcohol effect of moderate size.…”
Section: Introductionmentioning
confidence: 92%
“…Most studies reported an inverse association between alcohol consumption and the risk of ML (1)(2)(3)(4)(5)(6), but reported inconsistent results with regard to that of PCM (6)(7)(8)(9). In contrast to the number of studies in Western populations, however, little research has been conducted in Asian populations.…”
Section: Introductionmentioning
confidence: 99%